Agroecological specificities agriculture of sandy soddy-podzolic soils Belarus - Kulikov, Yaroslav K. (Experimental Biology and Biotechnology, 2017)
A high efficiency of the single application of peat-manure compost and loam for optimizing the properties of sandy soddy-podzolic soil was shown. The scolded improvement of sandy soil is reached by significant increase of the content of the physical clay and humus, and its qualitative composition improvement as well. Thereupon the agrochemical characteristics and water regime of soil are improved, as well as the biological activity increased. Optimized soil provided for the high and stable yield of agricultural crops regardless of weather impacts.
Keywords: peat fertilization; earthing; sandy soil; peat-manure compost; loam; water-holding capacity; clay; humus; porosity; microbiological diversity; biological activity